2016
DOI: 10.1021/acs.iecr.6b00627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Operating Conditions in the Transformation of DME to olefins over a HZSM-5 Zeolite Catalyst

Abstract: The effect of the operating conditions (cofeeding methanol and water, temperature, space time, and feed concentration) on the reaction indices of the transformation of dimethyl ether (DME) to light olefins has been studied, using a HZSM-5 zeolite catalyst (SiO 2 /Al 2 O 3 molar ratio of 280) agglomerated with boehmite and alumina. The experiments have been carried out in an isothermal fixed bed reactor under the following conditions: 300− 400 °C, space time, 0.2−6 g cat h mol C −1 ; feed, pure DME, and diluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 55 publications
3
37
0
2
Order By: Relevance
“…For H-ZSM-5, it has been reported that DME is converted to hydrocarbon more quickly than methanol, but there has not yet been a thorough deactivation study comparing both oxygenates [47,105]. Remarkably, the group of Bilbao has shown that addition of methanol and water to a DME feed over H-ZSM-5 interestingly leads to lower initial activity of the catalyst, thereby supporting faster MTH kinetics for DME compared to methanol [177,178].…”
Section: Catalyst Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…For H-ZSM-5, it has been reported that DME is converted to hydrocarbon more quickly than methanol, but there has not yet been a thorough deactivation study comparing both oxygenates [47,105]. Remarkably, the group of Bilbao has shown that addition of methanol and water to a DME feed over H-ZSM-5 interestingly leads to lower initial activity of the catalyst, thereby supporting faster MTH kinetics for DME compared to methanol [177,178].…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…Furthermore, adding water to methanol or DME feeds has been shown to have a positive effect in catalyst stability over different zeolitic catalysts [177][178][179][180][181][182], very likely due to the strong competition of water with methanol, DME and hydrocarbons for the acid sites, and therefore helping to avoid the retention of coke molecules [183].…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…The bed consists of a mixture of catalyst and inert particles (silicon carbide). The reactions were carried out feeding pure DME (18 mL·min −1 ) at temperature of 325-375 • C, pressure of 1.5 atm, space times of 4 g·h·mol C −1 , during 18 h. A reaction co-feeding water has been carried out using a molar ratio H 2 O/DME 3.55 [56]. Prior to the reaction, the transformation of DME (very sensitive to the presence of water) requires an in situ conditioning treatment of the catalyst (at 550 • C with air for 2 h) in order to eliminate the water adsorbed in the acid sites of the catalyst.…”
Section: Reaction and Analysis Equipmentmentioning
confidence: 99%
“…Besides, DME is a potential raw material for the production of diesel fuels (such as dimethoxymethane and polyoxymethylene dimethyl ethers, via oligomerization) [4], and chemicals (methyl acetate, formaldehyde, ethanol, among others) [5], replacing methanol. Moreover, it can replace methanol for light olefin production [6,7] and it is a H 2 vector through steam reforming [8][9][10].…”
Section: Introductionmentioning
confidence: 99%